2010
DOI: 10.1016/j.matlet.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of perforation of glass/polyester structures subjected to high-velocity impact

Abstract: a b s t r a c t a r t i c l e i n f o Keywords:Composite materials Sandwich Multiplate structure Impact behaviour Aerospace materialsIn this paper the ballistic behaviour of several glass/polyester laminate structures was studied, evaluating the residual velocity of the projectile and the damage area. Three monolithic laminates of different thicknesses and two multiplate laminate structures were analyzed: one of a sandwich type with face sheets of glass/ polyester and a foam core, and another made with the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 6 publications
2
36
0
Order By: Relevance
“…These two values were selected because the model was previously compared with experimental results for both areal densities. 8,26 For both laminates, it can be seen that for impact energy below the perforation threshold the absorbed energy is a linear function of the impact energy, because all the energy of the projectile is absorbed. For these impact energies, the main mechanisms of absorbed energy are the fibre elastic deformation and the fibre failure.…”
Section: Resultsmentioning
confidence: 98%
“…These two values were selected because the model was previously compared with experimental results for both areal densities. 8,26 For both laminates, it can be seen that for impact energy below the perforation threshold the absorbed energy is a linear function of the impact energy, because all the energy of the projectile is absorbed. For these impact energies, the main mechanisms of absorbed energy are the fibre elastic deformation and the fibre failure.…”
Section: Resultsmentioning
confidence: 98%
“…Naik and Shrirao [16] compared ballistic impact behavior of plain weave E-glass/epoxy and twill weave carbon/epoxy composites and concluded that ballistic limit is higher for plain weave E-glass/epoxy than the latter. Buitrago et al [17] performed high velocity impact tests on E-glass/polyester laminates using spherical steel projectiles and found that the ballistic limit and the extent of the damage area increased with the thickness of the monolithic laminates. The effect of target thickness on ballistic performance of E-glass/epoxy and ultra high molecular polyethylene composites against FSPs has been studied and found to have bi-linear relationship between the target thickness and energy absorption [18, Materials and Design 84 (2015) [21] carried out parametric study on E-glass/polyester composites using 9 mm ogive and conical shaped lead projectiles and the results were compared with mathematical model and showed good agreement between the two correlations.…”
Section: Introductionmentioning
confidence: 99%
“…9a), the energy absorbed by delamination and matrix cracking rise slightly with the density ratio, due to the increase ofĜ IICD andÊ MT (Eqs. (12) and (13)). …”
Section: Influence Of the Density Ratiomentioning
confidence: 94%
“…The data used was from high velocity impact tests on E glass/polyester plain woven lami nates, with a geometry ratio of 0.85 and 1.60, impacted by spherical steel projectiles 7.5 mm in diameter [12,20]. Table 1 shows the mechanical properties of this laminate, which registered at high strain rates [1,26,27].…”
Section: Experimental Validationmentioning
confidence: 99%